Experience and kerygma a critical study of Jose M. De Mesa's contextual theological model - Canlas, Reshley Ramon M.; De Mesa, Jose M. Contextual theological model (Quezon City Giraffe Books, 2008)
"The main task of this book is to evaluate the model of Dr. Jose M. de Mesa's model of doing contextual theology whether this is consistent with the experience and kerygma and of the Church."--Introduction.
Chapter I. An overview of the translation, anthropological and praxis models of contextual theology as presented by Stephen B. Evans -- Chapter II. Jose M. De Mesa : the person and presuppositions of his model of doing contextual theology -- Chapter III. Jose De Mesa's hermeneutics of appreciation : with a view to kerygma -- Chapter IV. Critique of De Mesa's hermeneutical keys : experience and kerygma.
Originally presented as a doctoral dissertation in the Faculty of Sacred Theology of the Royal and Pontifical University of Santo Tomas, Manila.
Keywords: Theology -- Methodology; Experience (Religion); Kerygma; Christianity and culture -- Philippines